Livestock's role in Africa's food security and crop production - Gelan, Ayele (International Livestock Research Institute, 2012)
Speaking at the Increasing Agricultural Productivity and Enhancing Food Security in Africa conference held in Addis Ababa, Ethiopia 1-3 November, 2011, ILRI's Ayele Gelan discusses ways to integrate livestock in the CAADP framework. He also discusses how livestock is neglected when it comes to policy making compared to crops.